ANALISIS PENGARUH FAKTOR-FAKTOR MAKROEKONOMI DAN KINERJA PENGELOLAAN ZAKAT TERHADAP KEMISKINAN DI INDONESIA - Listy Nur Ajizah (2023)
Poverty is still a problem that is difficult to overcome in Indonesia. Although Indonesia is a rich country in natural resources. Therefore, this study aims to analyze several factors that can affect poverty such as economic growth, the Human Development Index, income distribution inequality, and zakat management performance. This study uses secondary data with panel data regression as a data analysis technique. Then the sample for this research is 16 provinces in Indonesia that have a population poverty percentage of above ten percent from 2018-2021. The results of this study indicate that the variables of economic growth, the Human Development Index, inequality of income distribution, and the performance of zakat management jointly influence the poverty. Meanwhile, partially, this study found that only the Human Development Index affects poverty. Therefore, this research implies that by improving the quality of human resources, the poverty of the population in 16 provinces in Indonesia can be overcome.